A bioanalytical assay to distinguish cellular uptake routes for liposomes. (9th November 2015) - Braun, Tobias; Kleusch, Christian; Naumovska, Elena; Merkel, Rudolf; Csiszár, Agnes
Abstract: Lipid‐based nanoparticles are frequently used for drug or DNA delivery into mammalian cells. However it is difficult to determine whether such particles are taken up via endocytosis or fusion to the plasma membrane. Here, we propose a simple and reliable analytical method to do so based on the unique spectral properties of the fluorescent tracer BODIPY FL. At high local concentrations, this dye displays an additional red‐shifted emission peak that is absent at low concentrations. In dye‐loaded liposomes taken up by endocytosis, the local dye concentration did not significantly change upon internalization. Accordingly, unchanged fluorescence spectra were detected. When cells were incubated with liposomes able to fuse with the plasma membrane of mammalian cells, a reduction of local dye concentration and much weaker emission in the red‐shifted peak were observed. The ratio of intensities in both fluorescence channels was shown to be a reliable indicator of the cellular uptake mechanism. © 2015 International Society for Advancement of Cytometry